ANALYSIS OF CAPITAL ADEQUACY IN ASSESSING INVESTMENT ATTRACTIVENESS OF COMMERCIAL BANKS - Urokboyeva Farzuna Akhmadjonovna (American Journals, 2025)
In the world, many methods and methods are used to assess the investment attractiveness of commercial banks. The most widely used method is the CAMELS method or rating system. In this article, we will analyze the investment attractiveness of several banks in our country through capital adequacy, which is a component of the CAMELS method, and study the role of capital adequacy in increasing investment attractiveness.
Keywords: Investment attractiveness, capital adequacy, regulatory capital, risk-adjusted assets